Fruit-Based fermented beverages: Contamination sources and emerging technologies applied to assure their safety - Avîrvarei, Alexandra Costina (2023)
The food and beverage market has become broader due to globalization and consumer claims. Under the umbrella of consumer demands, legislation, nutritional status, and sustainability, the importance of food and beverage safety must be decisive. A significant sector of food production is related to ensuring fruit and vegetable conservation and utilization through fermentation. In this respect, in this review, we critically analyzed the scientific literature regarding the presence of chemical, microbiological and physical hazards in fruit-based fermented beverages. Furthermore, the potential formation of toxic compounds during processing is also discussed. In managing the risks, biological, physical, and chemical techniques can reduce or eliminate any contaminant from fruit-based fermented beverages. Some of these techniques belong to the technological flow of obtaining the beverages (i.e., mycotoxins bound by microorganisms used in fermentation) or are explicitly applied for a specific risk reduction (i.e., mycotoxin oxidation by ozone). Providing manufacturers with information on potential hazards that could jeopardize the safety of fermented fruit-based drinks and strategies to lower or eliminate these hazards is of paramount importance.